2015
DOI: 10.1136/jech-2015-205719
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chronic health problems and work-related factors on loss of paid employment among older workers

Abstract: All health problems affected disability benefits to a similar extent, but psychological health problems especially predicted unemployment and early retirement. For older workers with health problems, promoting an optimal work environment has the potential to contribute to sustainable employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 35 publications
7
86
1
Order By: Relevance
“…Yet, the percentage of people re-entering the work force is relatively low, ranging from roughly 30% for unemployed to 1% for early retirement. These numbers are similar to what has previously been reported in other studies (8,49).…”
Section: Strengths and Limitationssupporting
confidence: 93%
See 3 more Smart Citations
“…Yet, the percentage of people re-entering the work force is relatively low, ranging from roughly 30% for unemployed to 1% for early retirement. These numbers are similar to what has previously been reported in other studies (8,49).…”
Section: Strengths and Limitationssupporting
confidence: 93%
“…The relation between poor health and disability benefit is not surprising since a declined health is one of the essential requirements for receiving such a benefit. Furthermore, our results corroborate findings from previous research (1,(7)(8)(9). Various studies have reported a relation between poor health and the exit route of unemployment (eg, 41, 42).…”
Section: Influence Of Poor Health On Exit From Paid Employmentsupporting
confidence: 92%
See 2 more Smart Citations
“…In Denmark, 34.9% of the adult population report having at least one chronic disease and the prevalence increases with age (2). As the elderly accounts for an increasing proportion of the total population in most western societies, the age of the general workforce is rising (3,4). Because of the strong association between chronic disease and age (2,5), the proportion of workers with poor health is growing.…”
mentioning
confidence: 99%